2014
DOI: 10.1589/jpts.26.583
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance, Balance, Mobility, and Muscle Strength Decline at Different Rates in Elderly People

Abstract: [Purpose] The aim of this study was to verify the decline in functionality of elderly people. [Subjects and Methods] The study subjects comprised 152 individuals (96 women; 56 men) divided into 3 groups: G1 (60 to 69 years, n=53); G2 (70 to 79 years, n=65); and G3 (80 years or older, n=34). Physical performance, balance, mobility, and muscle strength were assessed using Short Physical Performance Battery (SPPB), Berg Balance Scale (BERG), Timed Up and Go (TUG) test, and leg press test, respectively. Comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 16 publications
1
35
0
7
Order By: Relevance
“…Nakano et al demonstrated that female patients in their 70s show a significant decline in functionality, i.e., physical performance and balance, as compared to their male peers. Older females display greater loss of muscle mass and muscle strength, which predisposes to frailty syndrome18 ) . Duckham et al showed that males over 65 had significantly greater rates of outdoor falls while engaging in recreational or vigorous activities.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al demonstrated that female patients in their 70s show a significant decline in functionality, i.e., physical performance and balance, as compared to their male peers. Older females display greater loss of muscle mass and muscle strength, which predisposes to frailty syndrome18 ) . Duckham et al showed that males over 65 had significantly greater rates of outdoor falls while engaging in recreational or vigorous activities.…”
Section: Discussionmentioning
confidence: 99%
“…SPPB was used to evaluate the performance of lower limbs in three aspects: muscle strength, gait and balance [30]. The test consisted of three small tests: the first assesses static balance in three positions (the feet together in side-by-side, semi-tandem and tandem positions); the second assesses gait speed, timing how long it takes to go three meters at a normal pace; the third evaluates the strength of the lower limbs, clocking time to rise from a chair and return to the seated After the experimental period, the intragroup evaluation demonstrated a significant increase of 26.6% (PG) and 40.3% (AG) in the distance walked in 6MWT (p = 0.001).…”
Section: Short Physical Performance Battery (Sppb)mentioning
confidence: 99%
“…Aging is associated with a decline in mobility and balance, which may lead to falls and a loss of independent function [1]. One possible mechanism of these impairments in older adults is an increase in lower extremity muscle co-contraction.…”
Section: Introductionmentioning
confidence: 99%